The Limits of International Justice: International Criminal Court Effectiveness in Genocide Cases - Safira Embun Insanidya; Ridwan Arifin; Wildan Azkal Fikri (Faculty of Law, Universitas Sembilanbelas November Kolaka, 2025)
This article examines the limits of international justice by assessing the effectiveness of the International Criminal Court (ICC) in prosecuting genocide. Despite its establishment as a permanent tribunal to end impunity for the most serious international crimes, the ICC faces persistent structural, political, and legal challenges that constrain its performance. Drawing on legal effectiveness theory, this study analyzes the extent to which the ICC fulfills its mandate in genocide cases by evaluating key factors such as jurisdictional limitations, state cooperation, evidentiary barriers, and prosecutorial strategy. Using a normative juridical method combined with selected case studies, the article demonstrates that the ICC’s effectiveness is uneven and often dependent on external political will rather than purely legal mechanisms. While the Court has contributed to the development of international criminal law and symbolically reinforced accountability norms, its practical impact on deterring and prosecuting genocide remains limited. The reliance on state cooperation, selective enforcement, and geopolitical considerations frequently undermines its authority and reach. The article argues that the ICC’s challenges are not merely institutional but reflect broader tensions within the international legal order. Strengthening the Court’s effectiveness requires not only procedural reforms but also deeper commitment from states and international actors to uphold accountability for genocide. Ultimately, the ICC represents both a significant achievement and a constrained instrument of international justice.